Genetic diversity and differentiation in natural Plasmodium falciparum populations inferred by molecular typing of the merozoite surface proteins 1 and 2 - Pereira,Fabrício J.T. (2002)
Genetic diversity and differentiation, inferred by typing the polymorphic genes coding for the merozoite surface proteins 1 (Msp-1) and 2 (Msp-2), were compared for 345 isolates belonging to seven Plasmodium falciparum populations from three continents. Both loci yielded similar estimates of genetic diversity for each population, but rather different patterns of between-population differentiation, suggesting that natural selection on these loci, rather than the transmission dynamics of P. falciparum, determines the variation in allele frequencies among populations.